’De schoone staat van Nederland’ - Meyer, H. (BMGN - Low Countries Historical Review, 2008)
The Pristine State of the NetherlandsThe main benefit of Van der Woud’s book is its detailed description of the process of physical unification of the new Dutch nation state through the establishment of an infrastructure for traffic, transport and communication. This new infrastructure was accompanied by a radical change in the appearance of the Dutch landscape. Increasingly during the nineteenth century, the ‘authenticity’ and ‘unique character’ of the Dutch landscape came to be valued and respected. Those who supported this ideal of ‘authenticity’ would have been horrified at the establishment of a new infrastructure. It is highly probable that this critique was a response to the new aesthetic of the modern infrastructure. It therefore comes as a surprise to this author that Van der Woud did not focus on this controversy at all. This review is part of the discussion forum 'Een nieuwe wereld' (A. van der Woud).